(untitled) (Research, Society and Development, 2020)
Happiness is an important topic in the history of philosophy and from ancient times in Greece to the present day the subject is discussed and has been brought up today in the great discussions of society. The aim of the work is to question what happiness is, how to achieve it and whether this concept has changed over the course of history, given that every human being aspires to be happy. We will try to answer these questions based on our author André Comte-Sponville, who dedicates most of his life, as a philosopher, to the theme of happiness with the work “happiness desperately” that addresses the concept of happiness and how it changed in the course of of time. It is concluded that the contemporary world seeks happiness at all costs. We live in the moment when we are bombarded by consumerism and we are deluded that happiness is found in the goods and pleasures of life. For the author, happiness is found in the continuous action of the person who acts in the fulfillment of desire, insofar as it is subordinated to right reason. We understand that happiness, as the ultimate goal that we seek, is in man’s own will to realize it, in the deliberate choice we make and not in the object through which we seek to achieve it, which we desire and want. Sponville still invites us to a true conversion of desires, that we move away from the vicious circle of hope that imprisons us to an unhappy and not genuine life. We need to desire what we do not lack, the real.